Not for free / Saul J. Berman - Saul J. Berman
'Not For Free' will not substitute for a top-level MBA; however, it does update thinking on important marketing dimensions utilizing recent examples. Author Berman contends that nearly every industry is susceptible to widely available low-cost disruptions originating from low-cost communications, data-processing, rapid innovation, and great increased consumer expectations. For example, record companies lost 40% of their revenues since 2000, newspapers 85% of their classified revenues from print editions between 2005-2009, and long-distance telecommunications revenues dropped 80% in the first decade of the new millennium. Further, markets have become increasingly fragmented recently, thanks to increased choices (eg. # of channels), new options - via new technology (eg. Netflix offering both mail and Internet delivery of movies, kiosks are another new option).